TAKING DUE CARE: MORAL OBLIGATIONS IN DUAL USE RESEARCH - Kuhlau, Frida (Bioethics, 2008)
In the past decade, the perception of a bioterrorist threat has increased and created a demand on life scientists to consider the potential security implications of dual use research. This article examines a selection of proposed moral obligations for life scientists that have emerged to meet these concerns and the extent to which they can be considered reasonable. It also describes the underlying reasons for the concerns, how they are managed, and their implications for scientific values. Five criteria for what constitutes preventable harm are suggested and a number of proposed obligations for life scientists are considered against these criteria, namely, the obligations to prevent bioterrorism; to engage in response activities; to consider negative implications of research; not to publish or share sensitive information; to oversee and limit access to dangerous material; and to report activities of concern. Although bioterrorism might be perceived as an imminent threat, the analysis illustrates that this is beyond the responsibility of life scientists either to prevent or to respond to. Among the more reasonable obligations are duties to consider potential negative implications of one's research, protect access to sensitive material, technology and knowledge, and report activities of concern. Responsibility, therefore, includes obligations concerned with preventing foreseeable and highly probable harm. A central conclusion is that several of the proposed obligations are reasonable, although not unconditionally.